DESAIN DAN IMPLEMENTASI LAYANAN PENYEDIA DATA PENERIMAAN MAHASISWA BARU BERBASIS WEB SERVICES UNTUK MENUNJANG EXECUTIVE SUPPORT SYSTEM - Kenali, Eko Win (Jurnal Informatika, 2013)
A design and implement a data provider services (services provider) new admissions web-based services to support the needs of data for executive support system without reducing the workload of academic database server, ensure interoperability and security systems in Lampung State Polytechnic. With the data provider services (services provider) is a web-based services, the future of academic data base server can be accessed and processed using a multi-platform applications.Methods floating system used in this study are the method of software engineering approach, Linear Models. Starting with the analysis, to collect and analyze data through field studies. Later stages of the design, architectural design services for data providers, data design, interfaces and applications required. The next stage is the implementation of the service architecture design data providers (services provider) web-based services, data, interfaces and applications implemented on the real or actual conditions. The final step is testing the method of black box testing, test architecture for service providers warrant the entire system runs well and fitKeywords: Data, Web Services, services providers, push.